2018
DOI: 10.1002/ccr3.1929
|View full text |Cite
|
Sign up to set email alerts
|

Fatal right‐sided heart failure due to leukostasis in a patient with leukemic transformation of myelodysplastic syndrome

Abstract: Key Clinical Message We document leukostasis leading to acute fatal right‐sided heart failure. In patients presenting with leukostasis and cardiopulmonary symptoms, clinicians should aim to assess for cardiac involvement, that is, by ECG and acute echocardiogram, since early recognition of right ventricular disease may provide an opportunity to treat this potentially reversible condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Some rare abnormalities include deep vein thrombosis, splenic rupture, or acute kidney injury [15][16][17][18]. Pryds et al [18] reported a case with right heart failure, which had similar echocardiographic findings to the present case. In the present case, various mechanisms of death could be considered, including respiratory or hepatic failure due to accumulated blasts, an acute heart failure as Pryds et al suggested, or a combination of these conditions.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Some rare abnormalities include deep vein thrombosis, splenic rupture, or acute kidney injury [15][16][17][18]. Pryds et al [18] reported a case with right heart failure, which had similar echocardiographic findings to the present case. In the present case, various mechanisms of death could be considered, including respiratory or hepatic failure due to accumulated blasts, an acute heart failure as Pryds et al suggested, or a combination of these conditions.…”
Section: Discussionsupporting
confidence: 78%
“…Common symptoms are dyspnea, confusion, headache, tinnitus, blurred vision, or focal neurologic deficits [16]. Some rare abnormalities include deep vein thrombosis, splenic rupture, or acute kidney injury [15][16][17][18]. Pryds et al [18] reported a case with right heart failure, which had similar echocardiographic findings to the present case.…”
Section: Discussionsupporting
confidence: 71%
“…Acute right heart failure has been less frequently described as a cause of acute cardiovascular collapse in patients with leucostasis 10 11. Katogiannis et al described the case of a 59-year-old woman who died shortly after presenting with dyspnoea for 2 days in the setting of newly diagnosed chronic myeloid leukaemia and a white blood count of 390 000/µL 10.…”
Section: Discussionmentioning
confidence: 99%
“…The most common clinical manifestations of leucostasis are neurological and respiratory symptoms, though several organ systems can be affected 3 5 6 8 9. Acute cardiovascular collapse may be an early finding 10–12…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, cardiac involvement accounted for 6% of cases [3]. Besides myocardial infarction, there have been case reports of leukocytosis causing cardiac failure as well [4,5].…”
Section: Discussionmentioning
confidence: 99%